The Uses of Exposed Raw Materials in Construction: A Stratigraphical and Geochemical Outcome of Zallah Sheet - El Ebaidi S. K; Al Faitouri M; Muftah A. M (Scientific Journal of University of Benghazi, 2026)
The Zallah Sheet (NH 33 – 16) area is studied by the Industrial Research Center, and it has a large industrial significance. Throughout the detailed study conducted on the chemical analysis of the sedimentary rocks, the main use of these rocks in construction and building materials includes all of the dimension blocks, natural aggregates, crushing aggregates, concretes, and paving road-stones. However, the manufacture of refractory bricks and Portland cement where the main components of available limestone and clay raw materials. A recalculation for the chemical analyses has been used to determine the limestone and clay percentages for manufacturing Portland cement. The raw materials mentioned above are existing in the following formations (from oldest to youngest); Rawaghah Member of the Bishimah Formation (Ypresian), Al Jir Formation (Lutetian), Thmed al Qusur Member of the Wadi Thamat Formation (Priabonian) and Qarat Jahannam Member of Maradah Formation (Aquitanian - Burdigalian).